Clinical Measures of Pelvic Tilt in Physical Therapy - William H. Suits (International Journal of Sports Physical Therapy)
Pelvic tilt refers to the spatial position or motion of the pelvis about a frontal horizontal axis on the rest of the body in the sagittal plane. It is relevant for several musculoskeletal conditions commonly seen in physical therapist practice, particularly conditions affecting the hip and groin. Despite the relevance of pelvic tilt identified in biomechanical studies, and the historical precedence for assessing pelvic tilt, there is a lack of clarity regarding the utility of clinical measures that are practical in a rehabilitation setting. There are several options available to assess pelvic tilt which are discussed in detail in this commentary. All of these options come with potential benefits and considerable limitations. The purpose of this commentary is to provide an overview of the relevance of understanding pelvic tilt in the pathology and rehabilitation of conditions affecting the hip joint, with a focus applying evidence towards identifying clinical measures that may be useful in the rehabilitation setting and considerations that are needed with these measures.